2013
DOI: 10.1159/000356614
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 Inhibits Proliferation of Mouse Pancreatic Progenitor Cells by Targeting YAP1

Abstract: Background/Aims: The Hippo signaling pathway regulates expansion and differentiation of stem cells and tissue progenitor cells during organ development and tissue regeneration. Previous studies have shown that YAP1, a potent effector of the Hippo signaling pathway, plays a crucial role in pancreas development, but the function of YAP1 in pancreatic progenitor cells is less known. Methods: The spatio-temporal expression pattern of YAP1 in mouse developing pancreata was detected by in situ hybridization. The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…miR-375 was primary identified in the human pancreas in 2004 (36), and Avnit-Sagi et al (37) suggested that miR-375 was expressed at a very high level in human pancreatic islets and brain tissue. Previous studies also identified that miR-375 was involved in numerous types of cancer (38)(39)(40): The expression of miR-375 was downregulated in human gastric cancer cells, and the induction of miR-375 expression may affect the biological function of cells (41); Zhang et al (42) also identified that miR-375 expression was abnormally regulated in pancreatic progenitor cells, and that the regulation of miR-375 expression may inhibit cell proliferation through targeting Yes associated protein 1. However, the biological effect of miR-375 in human liver cancer has not been fully studied.…”
Section: Discussionmentioning
confidence: 99%
“…miR-375 was primary identified in the human pancreas in 2004 (36), and Avnit-Sagi et al (37) suggested that miR-375 was expressed at a very high level in human pancreatic islets and brain tissue. Previous studies also identified that miR-375 was involved in numerous types of cancer (38)(39)(40): The expression of miR-375 was downregulated in human gastric cancer cells, and the induction of miR-375 expression may affect the biological function of cells (41); Zhang et al (42) also identified that miR-375 expression was abnormally regulated in pancreatic progenitor cells, and that the regulation of miR-375 expression may inhibit cell proliferation through targeting Yes associated protein 1. However, the biological effect of miR-375 in human liver cancer has not been fully studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the Hippo-YAP pathway provides a new method for cancer treatment in clinical studies [37, 38]. However, the application of this signaling pathway to the treatment of ovarian diseases has not been tested.…”
Section: Discussionmentioning
confidence: 99%
“…As major downstream effectors, TEAD and its coactivator YAP play a crucial role in the expansion of pancreatic progenitors by controlling key pancreatic signaling mediators and transcription factors in the embryonic phase of pancreas development (27). Consistently, YAP depletion is sufficient to block pancreatic progenitor cell proliferation (30). However, convincing studies have revealed that YAP is not expressed in terminally differentiated mature primary human and mouse β cells.…”
Section: Introductionmentioning
confidence: 99%